Performance Based on Civil Servant Allowances at the Makassar Tourism Polytechnic - Rohman, Irva Yulia; Akib, Haedar; Niswaty, Risma (Universitas Negeri Makassar, 2023)
Performance is the result of a process that is referred to and measured over a certain period of time based on previously established provisions or agreements. Furthermore, the institution will gain many benefits from the good performance of civil servants because it can optimize the function of services provided to the community. This research aims to examine the performance of civil servants at the Makassar Tourism Polytechnic with a focus on educational institutions under the auspices of the Ministry of Tourism, namely the Makassar Tourism Polytechnic. Data collection techniques were carried out by means of observation, interviews and documentation. The data analysis technique used is the Miles and Huberman model analysis consisting of data collection, data condensation, data presentation and drawing conclusions. The results of the research show that Allowance-Based Performance at the Makassar Tourism Polytechnic has been implemented in accordance with the regulations of the creative economy ministry of tourism. Then, if we look at the supporting factors, the government's policy in providing civil servant performance allowances has been included in the Minister of Tourism and Creative Economy Regulations. The inhibiting factor in this allowance-based performance is the lack of awareness of some employees regarding their mastery of computer technology as well as the lack of awareness of employees in understanding the importance of being on time at work. This research can be used as a reference and knowledge about civil servant allowance-based performance using qualitative research methods.